Survey of sheep antibodies of smooth and rough strains of brucella in the north patagonic area of La Pampa - Meglia, Guillermo Esteban; Gastaldo, Marcelo Fabian; Oriani, Delia Susana; Dubarry, Jorge Roberto; Alvarez Rubianes, Nicolas Maria Jose (Ciencia Veterinaria, 2017)
Brucellosis is an infectious disease that affects domestic animals, producing heavily losses through abortions, and infertility in rams.The flock epidemiology situation in the north Patagonic area of Argentina (La Pampa) to the present disease is unknown; consequently the objective was to determine the prevalence of the disease. Out of 10.000 sheep, there were sampled 1.800 animals according to the application of the minimum sample size for estimating a rate with specified degree of precision in the Departments of Mara-co, Chapaleufu, Realico, Rancul, Conhelo and Quemu-Quemu representing an area of 22.072 km2, in the frame of reintroduction of sheep production in the province. Independently of the number of sheep per farm, 20- 30% of the flock was sampled, that represent 15% (270) rams and 85% (1.530) ewes. After collecting serum from jugular blood, the samples were analysed either for the presence of antibodies against smooth strain through Buffer Plate Agglutination Test (BPA); or antibodies against rough strain of brucella through Agar Gel Immuno-diffusion Test (AGID). Bewilderment of all the animals was negative to both tests. Despite brucellosis is a high prevalent infectious di-sease in other part of the country, these results emphasise the condition of free areas of the disease.